Evaluation of controlled vocabulary for the representation and recovery of theses and dissertations in institutional repository - Alves, Lizandra de Souza Santos [UNESP]; Tartarotti, Roberta Cristina Dal'Evedove; Fujita, Mariangela Spotti Lopes [UNESP] (Univ Brasilia, Dept Ciencia Informacao, 2022)
Objective: The research aimed to carry out an evaluation of the theses and dissertations vocabulary control in the Institutional Repository of the Sao Paulo State University (UNESP), whose methodological procedures were outlined in an exploratory-explanatory research with a case study. Methodology: For this, evaluation criteria were applied in two categories of analysis: intrinsic evaluation, containing criteria aimed at the repository itself and extrinsic evaluation, with criteria aimed at the analysis of representation and information retrieval. Results: The results showed that the Institutional Repository of the Sao Paulo State University (UNESP) needs greater terminological control of the terms correlated to the research of theses and dissertations for greater precision in the retrieval of informational resources. Conclusion: The lack of standardization in the representation causes failures in the recovery, with inconsistencies in the interaction of the institutional repository with its users.
Keywords: Institutional repositories; Controlled vocabularies; Indexing evaluation; Subject retrieval